Red zone against blue men: tourism in French-Malian diplomatic relations - (:unkn) unknown (My University, 2013)
Panel Tourist mobilities in contemporary Africa, mod Nadège Chabloz et Anne Doquet http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2211
Keywords: African Research